Harga diri, dukungan sosial, dan kesejahteraan subjektif guru di daerah terpencil, terluar dan tertinggal: perspektif psikologi positif - Stiwi R.F. Nope; Rahma Widyana; Kamsih Astuti (Jurnal Konseling dan Pendidikan, 2025)
Working as a teacher in frontier, outermost, and underdeveloped (3T) regions presents psychological and environmental challenges that may affect teachers’ subjective well-being. Grounded in positive psychology, this study hypothesized that self-esteem and social support would be positively related to subjective well-being. Using a quantitative correlational survey design, data were collected from 154 teachers (64.3% female, aged 25–56 years, M = 39.8, SD = 7.6; average teaching experience = 11.4 years) across elementary to high school levels in Amabi Oefeto Timur District, Kupang Regency, East Nusa Tenggara. Instruments were administered offline in schools with institutional permission due to limited internet access. Instruments included the Teaching Satisfaction Scale (TSS), PANAS, Rosenberg Self-Esteem Scale, and R-MSPSS. Results indicated significant positive correlations between self-esteem and subjective well-being (r = 0.43, p < .01) and between social support and subjective well-being (r = 0.38, p < .01), with R² = 0.256. Teachers with higher self-esteem and stronger social support reported greater life satisfaction and positive affect, supporting the positive psychology and social buffering models. The findings emphasize the importance of self-esteem and social support enhancement programs for teacher well-being in resource-limited contexts. Ethical approval was obtained, and all participants provided informed consent. Limitations and directions for future research are discussed.